Pengaruh Budaya Organisasi Terhadap Kinerja Guru Sekolah Dasar Negeri Cengkong II Kecamatan Purwasari - Antika, Meri; Isyanto, Puji (LANCAH: Jurnal Inovasi dan Tren, 2024)
The aims of this research to determine and analyze the influence of organizational culture on the performance of Cengkong II Elementary School teachers in Kecamatan Purwasari. The research was carried out with the research objects being all teachers at SDN Cengkong II. The variables observed in this research are organizational culture and performance. This research analyzes data using the SPSS program. Data analysis includes simple linear regression, descriptive analysis, quantitative analysis, validity test, reliability test, and hypothesis test. The research results show that organizational culture factors have a significant influence on teacher performance at SD Negeri Cengkong II in Kecamatan Purwasari. Apart from that, organizational culture factors have a partial influence on teacher performance at SD Negeri Cengkong II, Kecamatan Purwasari.